Hadis Dalam Pandangan Sarjana Barat: Telaah Atas Pemikiran G.H.A. Juynboll - Syachrofi, Muhammad (Faculty of Ushuluddin and Religious Study, Universitas Islam Negeri Raden Intan Lampung, 2021)
AbstractThe study of hadith among Western scholars has developed quite significantly, especially after the appearance of Ignaz Goldziher with his work entitled Muhammedanische Studien. This development ultimately mapped the study of hadith in the West to become one-way. Western scholars have different thoughts from one another. Herbert Berg divides into three groups of Western scholars who study hadith based on their attitudes and thoughts, namely scepticism, sanguine, and middle ground. However, some experts in hadith studies only divide it into two groups, namely skeptics and non-skeptics. So, thus, there are differences of opinion regarding the position of some orientalists. For example, Juynboll was positioned by Herbert Berg in the middle ground group while other experts positioned him in the skeptical orientalist group. In order to explore this problem, the writer examines Juynboll's thoughts on the Prophet's hadith, especially in relation to the theory that is always embedded with his name, namely the common link theory. The author finds that Juynboll is not as skeptical as to his predecessors, who generalized the Prophet's hadith as questionable its authenticity. Juynboll still idealizes the existence of a hadith that can truly be accounted for its authenticity coming from the Prophet even though it is very small. That was why he was included by Herbert Berg in the middle ground group. AbstrakKajian hadis di kalangan para sarjana Barat mengalami perkembangan yang cukup signifikan terutama setelah munculnya Ignaz Goldziher dengan karyanya berjudul Muhammedanische Studien. Perkembangan tersebut pada akhirnya memetakan kajian hadis di Barat menjadi tidak satu arah. Para sarjana Barat memiliki pemikiran yang berbeda antara satu dengan lainnya. Herbert Berg membagi kepada tiga kelompok sarjana Barat yang mengkaji hadis berdasarkan sikap dan pemikirannya yaitu scepticism, sanguine, dan middle ground. Akan tetapi, sementara pakar kajian hadis hanya membagi kepada dua kelompok yaitu skeptis dan non-skeptis. Sehingga, dengan demikian, terdapat perbedaan pendapat mengenai posisi sebagian orientalis. Misalnya, Juynboll diposisikan oleh Herbert Berg dalam kelompok middle ground sementara pakar lain memosisikannya pada kelompok orientalis skeptis. Untuk mendalami permasalahan tersebut penulis menelaah kembali pemikiran Juynboll terhadap hadis Nabi terutama terkait dengan teori yang selalu disematkan dengan namanya yaitu teori common link. Penulis menemukan bahwa Juynboll tidak se-skeptis pendahulunya yang menggeneralisasi hadis Nabi sebagai sesuatu yang diragukan autentisitasnya. Juynboll masih mengidealkan adanya hadis yang benar-benar dapat dipertanggungjawabkan keotentikannya berasal dari Nabi meskipun itu sedikit sekali. Itulah mengapa dia dimasukkan oleh Herbert Berg ke dalam kelompok middle ground. Kata Kunci:Common link, hadis, Juynboll.